2020
DOI: 10.1126/sciadv.aay2671
|View full text |Cite
|
Sign up to set email alerts
|

Optothermotronic effect as an ultrasensitive thermal sensing technology for solid-state electronics

Abstract: The thermal excitation, regulation, and detection of charge carriers in solid-state electronics have attracted great attention toward high-performance sensing applications but still face major challenges. Manipulating thermal excitation and transport of charge carriers in nanoheterostructures, we report a giant temperature sensing effect in semiconductor nanofilms via optoelectronic coupling, termed optothermotronics. A gradient of charge carriers in the nanofilms under nonuniform light illumination is coupled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 35 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…The injection of holes into 3C-SiC also created a diffusion of these carriers to neighboring regions with lower hole concentration, resulting in a nonequilibrium condition. The Fermi level E f splits into two quasi-Fermi level, , hence the Femi-level in 3C-SiC was bent from electrode L to electrode R as shown in Figure -a. The Femi-levels in 3C-SiC ( E f,3C–SiC ) at the two electrodes are given by , where T is the temperature; k B is the Boltzmann constant (8.617 × 10 –5 eV.…”
Section: Resultsmentioning
confidence: 99%
“…The injection of holes into 3C-SiC also created a diffusion of these carriers to neighboring regions with lower hole concentration, resulting in a nonequilibrium condition. The Fermi level E f splits into two quasi-Fermi level, , hence the Femi-level in 3C-SiC was bent from electrode L to electrode R as shown in Figure -a. The Femi-levels in 3C-SiC ( E f,3C–SiC ) at the two electrodes are given by , where T is the temperature; k B is the Boltzmann constant (8.617 × 10 –5 eV.…”
Section: Resultsmentioning
confidence: 99%
“…However, there have been very limited reports on the effect of the temperature gradient on the photovoltaic effect of the SiC/Si heterostructure. Recent studies have shown the huge potential of the SiC/Si heterostructure for numerous sensing applications and devices such as photodetector, strain sensor, temperature sensor, position detector, and gas sensor . Due to the robustness of the SiC coating layer, the SiC/Si heterostructure-based sensors can work effectively in severe conditions. , Therefore, a comprehensive understanding of the sensing mechanism that governs the thermo-phototronic effect in the SiC/Si heterostructure will push forward its big potential as a microsensor for high-performance sensing systems as well as niche applications such as high operating temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…However, the high cost and small size of SiC wafers (e.g., 4H-SiC and 6H-SiC wafer) restrict the development of commercially available SiC devices. To overcome this limitation, cubic silicon carbide (3C-SiC), which can be grown on widely available Si wafers at a low cost, is receiving attention from researchers with numerous reports on 3C-SiC/Si heterostructure devices such as pressure sensors, strain sensors, and photodetectors. However, the potential of 3C-SiC/Si heterojunctions as a PSD has not been fully explored. To the best of our knowledge, only PSDs based on p-type 3C-SiC have been previously reported. …”
Section: Introductionmentioning
confidence: 99%